2018
DOI: 10.11648/j.jfns.20180604.11
|View full text |Cite
|
Sign up to set email alerts
|

Trends of Child Wasting and Stunting in Uganda from 1995 to 2016, and Progress Towards 65<sup>TH</sup> World Health Assembly Global Nutrition Targets

Abstract: Between 1995 and 2016, the government of Uganda ratified several commitments to fight child undernutrition including achieving the 65 th World Health Assembly (WHA) targets of reducing stunting and wasting by 2025. It is important we monitor such commitments to inform policy makers about the progress of their commitments. The objective of this study was to review national and regional trends of stunting and wasting in Uganda from 1995 to 2016, and assess progress towards the 65 th WHA global nutrition targets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Furthermore, these studies have shown slow annual stunting reduction rate of 0.45% which increases the chances of these children growing into stunted adults and this could partly explain the high proportions and increased odds of stunting in western and central regions seen in this study. An alternative explanation to these findings could be the fact that Western Uganda is partly inhabited by the Batwa tribe, an indigenous pygmy population who are relatively short (in height) compared to other Ugandans (48,49) and the possibility of migration of stunted women from other regions to the Central and Western regions which are the most economically vibrant regions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these studies have shown slow annual stunting reduction rate of 0.45% which increases the chances of these children growing into stunted adults and this could partly explain the high proportions and increased odds of stunting in western and central regions seen in this study. An alternative explanation to these findings could be the fact that Western Uganda is partly inhabited by the Batwa tribe, an indigenous pygmy population who are relatively short (in height) compared to other Ugandans (48,49) and the possibility of migration of stunted women from other regions to the Central and Western regions which are the most economically vibrant regions.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, a survey from 2016 showed that undernutrition is highly prevalent in rural Uganda [9], with 29% of children aged 6-59 months being stunted (i.e., low height-forage and a marker for chronic undernutrition), 4% being wasted (i.e., low weight-for-height and a marker for acute undernutrition), and 11% being underweight [10]. Statistics show that there was an overall decline in wasting and stunting prevalence between 1995 and 2016; however, the annual reduction rate of stunting and wasting was only 0.45% and 0.01%, respectively [11]. Notably, only a few interventions targeting nutrition have been implemented in Uganda [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In Uganda, the 2016 Demographic and Health Survey (DHS) shows 53%, 29% and 4% of 6-59-month-old children are anaemic, stunted and wasted, respectively, and only 15% of 6-23-month-old children are fed a minimum acceptable diet (UBOS, 2018). Even though these rates of stunted growth are high, they have declined from 38% in 1994 to 29% in 2016, which has been attributed in part to national efforts promoting nutrition interventions in the first 1000 days of life (Buzigi, 2018). This annual rate of decline, however, is too slow to achieve the 2025 World Health Assembly Global Nutrition targets, for Uganda, to reduce stunting by 40% (Buzigi, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Even though these rates of stunted growth are high, they have declined from 38% in 1994 to 29% in 2016, which has been attributed in part to national efforts promoting nutrition interventions in the first 1000 days of life (Buzigi, 2018). This annual rate of decline, however, is too slow to achieve the 2025 World Health Assembly Global Nutrition targets, for Uganda, to reduce stunting by 40% (Buzigi, 2018).…”
Section: Introductionmentioning
confidence: 99%